Asynchronous power grid DC blocking dynamic frequency monitoring and safety checking method - YANG RONGZHAO; WANG WEI; HUANG HANCHANG; ZHENG XIAODONG; LOU NAN; CHEN YIPING; CHEN JULONG; HOU JUN; GAO QIN; ZHANG YONG; WANG ZIQIANG; MO WEIKE (2017)
The invention discloses an asynchronous power grid DC blocking dynamic frequency monitoring and safety checking method comprising the following steps: acquiring required real-time power grid operation data from an energy management system; setting each DC line in an asynchronous power grid to a bipolar blocking state; according to the required real-time power grid operation data, using a frequency transient analysis method based on peak frequency estimation to judge whether high-frequency generator tripping occurs in each DC line after bipolar blocking under the control action of frequency regulation and security-stability solution of the system; and correspondingly treating the DC lines according to the judgment result of high-frequency generator tripping. According to the invention, a fault scene of bipolar blocking is set for each of the multiple DC lines in the asynchronous power grid, and the frequency transient analysis method based on peak frequency estimation is used. The peak frequency of the sender